Factors that Become a Dark Tourist Attraction in the Area of Mount Merapi Yogyakarta - Kallistus Brian Sadhana (International Journal Labs, 2022)
Background: In essence, dark tourism is a type of tourism that diverges because it is conceptually different from the concept of tourism in general. The concept of tourism is a vacation to find entertainment, but the concept of dark tourism is just the opposite, tourists who visit rarely find a pleasant impression. Purpose: This study aims to explain the motivation of tourists to visit dark tourism in the Mount Merapi area of Yogyakarta and describe the factors that become the attraction of dark tourism in the Mount Merapi area of Yogyakarta. Methods: This type of research uses qualitative methods. A research method used to study the state of natural objects, the resource person as a key instrument, the data collection technique is by triangulation, the nature of data analysis is inductive, and research results tend to prioritize benefits, not generalizations. Data retrieval techniques through on-site observation, unstructured interviews, and documentation in the form of references, citations, and images or photos. Data analysis techniques are by reducing data, then the data is arranged systematically, after that verification so that the data can be validated. Results: The results of the study explained that tourists have an interest in visiting dark tourism in the Mount Merapi area of Yogyakarta based on four motivations, namely; curiosity, exploration, self-reflection, and spirituality. Furthermore, six factors were found that became the dark tourist attraction in the Mount Merapi area of Yogyakarta: historical, new attractions, natural conditions, adventure, education, and myths. Conclusion: The results of the research and discussion that have been previously presented can be concluded that the first activity of tourists visiting dark tourism in the Mount Merapi area of Yogyakarta is a sense of curiosity.